POLICY AUDITS AND QUALITY MANAGEMENT SCHEMES RELATED TO THE ACCESSIBILITY OF PUBLIC TRANSPORT AND PUBLIC SPACE - Mikusova, Miroslava (Doprava a spoje, 2011)
The paper is aimed to carry out a comprehensive overview of the state-of-the-art regarding policy audits and quality management schemes, related to the accessibility of public transport and public space, including the success factors and features of these schemes. It is focused on general and much-used international standards and models as ISO 14 000 family, ISO 14 000 family, EMAS and the EFQM Excellence model, describing the general structure of the schemes, working process, covered areas and type of indicators used as well as the way that they address detailed content-related matters, related specifically to the ``public'' accessibility.